Physical-Chemical Characteristic and Trophic Status of Some Small Lakes in Ciliwung Watershed, West Java Indonesia - Siti Aisyah; Sulastri Sulastri; Rahmi Dina; Mey Ristanti Widoretno (Indonesian Society of Limnology, 2021)
Small lakes are important freshwater resources to support the quality of human life. However, small lakes in the watershed are becoming threatened ecosystems because of increasing land-use changes and anthropogenic activity. The study aimed to determine characteristic physical-chemical parameters and trophic status some small lake in Ciliwung Watershed to support the sustainable management of small lakes in the Ciliwung watershed in preventing eutrophication effects. The data was collected in April and June 2021. Measurement and analysis of water quality parameters were conducted by insitu and Laboratory. Some parameters were not in accordance with the Government Regulation number 22/2021 for class II water quality criteria (WQC), including TSS (>50 mg.L-1)., TP (>0.03 mg.L-1), COD (>25 mg.L-1) and DO (<3 mg.L-1), especially for Lake Sunter and Lake Cincin.There are two groups of lakes based on water quality and trophic status. Lake Telaga Warna Lake Cikaret, and Lake Cilodong were classified as eutrophic while lake Sunter and Lake Cincin were classified as hypereutrophic lake Lake Telaga Warna, Lake Cikaret, and Lake Cilodong, located at the upper and middle watershed, are eutrophic, characterized by deeper bottom and higher Secchi depth. At the lower watershed, Lake Sunter and Lake Cincin are hypereutrophic characterized by higher nutrients (TN and TP), COD, temperature, conductivity, salinity, and TDS. The downstream area was a densely populated area that contributed high pollution from upstream and middle of Ciliwung watershed.